Simulating water mixing in a barotropic estuary: the effect of vertical discretization - Martins, Flávio Augusto Bastos da Cruz (2009)
Mixing between estuarine and coastal waters is strongly dependent on the processes that occur in the vertical direction. This applies both for stratified and homogeneous estuaries. In homogeneous estuaries important recirculation flows in the vertical plane can arise, in regions with strong batimetry gradients, produced by the combined action of inertia and friction. On the Platform close to the inlet this structures can trap estuarine water during the ebb period, releasing it to the interior again during the flood.